2016
DOI: 10.1200/jco.2016.66.8459
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Depression Symptoms and Survival Among Patients With Lung Cancer: A National Cohort Assessment

Abstract: Purpose Depression symptoms are common among patients with lung cancer; however, longitudinal changes and their impact on survival are understudied. Methods This was a prospective, observational study from the Cancer Care Outcomes Research and Surveillance Consortium from five US geographically defined regions from September 2003 through December 2005. Patients enrolled within 3 months of their lung cancer diagnosis were eligible. The eight-item Center for Epidemiologic Studies Depression scale was administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
111
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 113 publications
(117 citation statements)
references
References 53 publications
5
111
1
Order By: Relevance
“…This was consistent with previous research which showed that baseline depression predicted 3-month and 6-month depression in a sample of newly diagnosed cancer patients; similarly, baseline anxiety predicted later anxiety [14]. However, compared to the specificity observed by HulbertWilliams and colleagues [14], the current study found that baseline clinical depression also predicted a six-fold increased risk of poor life satisfaction and a twelve-fold increased risk of clinical anxiety at 12-month follow-up.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…This was consistent with previous research which showed that baseline depression predicted 3-month and 6-month depression in a sample of newly diagnosed cancer patients; similarly, baseline anxiety predicted later anxiety [14]. However, compared to the specificity observed by HulbertWilliams and colleagues [14], the current study found that baseline clinical depression also predicted a six-fold increased risk of poor life satisfaction and a twelve-fold increased risk of clinical anxiety at 12-month follow-up.…”
Section: Discussionsupporting
confidence: 78%
“…Clinical depression and anxiety were not found to predict mortality. Our finding on depression and anxiety differed from studies which found support for the association between depression and mortality [8,14] as well as emotional distress (depression and anxiety) and mortality [15]. One possibility could be the presence of psychological resources such as hope, mindfulness, and spirituality [25][26][27].…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations